Microalgal Protein Extraction From Chlorella vulgaris FSP-E Using Triphasic Partitioning Technique With Sonication - Chia, S.R. (Frontiers Media S.A., 2019)
Green microalgae containing various bioactive compounds and macronutrients such as lipids, carbohydrates, and proteins, have attracted much attention from the global community. Microalgae has the potential to be applied in food industries due to its high protein content, rapid growth rate, and ability to survive in harsh conditions. This study presents a simple yet efficient technique of sonication-assisted triphasic partitioning process, also known as ultrasonic-assisted three phase partitioning (UATPP), for the extraction of proteins from Chlorella vulgaris FSP-E. Comparison studies between three phase partitioning (TPP) and UATPP was conducted to investigate the feasibility of the enhanced technique on proteins extraction. Types of salt, ratio of slurry to t-butanol, salt saturation, sonication frequency, power, irradiation time, and duty cycle as well as biomass loading were studied. UATPP was found to be an improved technique compared to TPP. An optimum separation efficiency and yield of 74.59 ± 0.45 and 56.57 ± 3.70 was obtained, respectively, with the optimized conditions: salt saturation (50), slurry to t-butanol ratio (1:2), sonication power (100), irradiation time (10 min), frequency (35 kHz), duty cycle (80) and biomass loading (0.75 wt). A scaled-up study was performed to validate the reliability of UATPP for protein extraction. The outcome of the study revealed that UATPP is an attractive approach for downstream processing of microalgae. © Copyright © 2019 Chia, Chew, Zaid, Chu, Tao and Show.